2015
DOI: 10.7763/ijet.2015.v7.777
|View full text |Cite
|
Sign up to set email alerts
|

A Model-Based Approach to Measuring the Effect of Shading on Outdoor Thermal Comfort

Abstract: Abstract-Building shading is a tried and true strategy for passive cooling to reduce energy consumption. But shading also affects the mobility system outside of buildings. This paper analyzes the effects of building shading on outdoor thermal comfort. It focuses on building height and density as the two design parameters of urban built form and uses weather data and passive shading simulation to derive a measure of the effect of walking outdoors. The model is specialized to regions of extreme heat and humidity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Baca and Tsai focused on analyzing the impact of the building shading on the OTC in Abu Dhabi, considering both the buildings' height and density. It was concluded that the optimum solution to improve the OTC is to increase the building height-to-width ratio [17]. Another study evaluated the outdoor evaporative surfaces in an outdoor campus courtyard in Abu Dhabi.…”
Section: Introductionmentioning
confidence: 99%
“…Baca and Tsai focused on analyzing the impact of the building shading on the OTC in Abu Dhabi, considering both the buildings' height and density. It was concluded that the optimum solution to improve the OTC is to increase the building height-to-width ratio [17]. Another study evaluated the outdoor evaporative surfaces in an outdoor campus courtyard in Abu Dhabi.…”
Section: Introductionmentioning
confidence: 99%